-6(3w-3)+2w=2(w+8)

Simple and best practice solution for -6(3w-3)+2w=2(w+8) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -6(3w-3)+2w=2(w+8) equation:



-6(3w-3)+2w=2(w+8)
We move all terms to the left:
-6(3w-3)+2w-(2(w+8))=0
We add all the numbers together, and all the variables
2w-6(3w-3)-(2(w+8))=0
We multiply parentheses
2w-18w-(2(w+8))+18=0
We calculate terms in parentheses: -(2(w+8)), so:
2(w+8)
We multiply parentheses
2w+16
Back to the equation:
-(2w+16)
We add all the numbers together, and all the variables
-16w-(2w+16)+18=0
We get rid of parentheses
-16w-2w-16+18=0
We add all the numbers together, and all the variables
-18w+2=0
We move all terms containing w to the left, all other terms to the right
-18w=-2
w=-2/-18
w=1/9

See similar equations:

| 2-x=9+2x | | -4(4x-2)+4x=9+3(2x-3) | | 3(2x+4)+2=-5x+25 | | 12-1,28(x-5)=22-2(x+4) | | 1+x/2-1/2-x/4+1/4=x/3+3/3 | | 3t+4=t13 | | 2x/4=x+3/3 | | 3x²=4x | | X²=2x | | 3z/10-4=3 | | (q-10)5=32 | | 5(q-10)=32 | | 4(e+5)=32 | | (x+6)(x-6)=10x+x*x-2*x*4+4*4 | | 2(x-2)+8=-2x+44 | | (3x+1)/4+(5x-2)/3=7 | | (4x)/(x+3)+12/(5x−3)=161/((5x−3)(x+3)) | | 4x^2-24+36=0 | | n/3+0.4=1 | | 4+y=–3 | | 3(2x+4)=4x-8 | | 5÷2y=10 | | √x+x=6 | | 3+(2x÷3)=-3 | | 8=2(x+4) | | (2x+3)+(3x-4)=0 | | 7p+4=–p+9+2p+3p | | 3x–7=4+6+4x | | 12d+8=100 | | X3+103=x9-5 | | x^2(x-6)(3x-1)=0 | | 9y-7=17-3y |

Equations solver categories